Genetic variability, character association and path analysis for quantitative traits to breed vegetable type cluster bean (Cyamopsis tetragonoloba) - Mishra, Smaranika; Aghora, T S; M, Senthil Kumar (The Indian Journal of Agricultural Sciences, 2020)
The present experiment was conducted during rabi 2017 at ICAR- Indian Institute of Horticultural Research, Bengaluru to assess the variability present in the germplasm and their usefulness in breeding of high yielding vegetable type cluster bean (Cyamopsis tetragonoloba L.). Total 38 diverse cluster bean germplasm from different sources were used to evaluate the variability, character association and their contribution towards pod yield. Characters like number of pods per plant, pod length, pod weight, plant height, number of clusters per plant, pods per cluster showed high coefficient of variations and high heritability with high genetic gain indicating their suitability for effective selection. Analysis of phenotypic and genotypic correlation co-efficient and path analysis revealed that traits like pod length, pod diameter, pod weight and seeds per pod had significant positive correlation with pod yield. Hence, selection for high pod weight with indirect selection for pod length will bring worthwhile improvement in yield.